1995
DOI: 10.1246/cl.1995.991
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopic Observations of Anomalous Conformational Behavior of Short Poly(oxyethylene) Chains in Water

Abstract: The Raman spectra of aqueous solutions of CH3(OCH2CH2)mOCH3 (m = 1−4) were measured for mole fractions down to 0.005. The spectral observation for the compounds with m ≥ 2 indicates that, on addition of water, the POE chain progressively prefers the gauche conformation for the OCH2–CH2O segment at the first stage, but this direction of the conformational preference is reversed for concentrations lower than a particular solution composition. This anomalous conformational behavior is suggestive of a new structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 11 publications
3
30
0
Order By: Relevance
“…Meot-Ner et al 29 examined the complexing of H + from the formation of intramolecular or intermolecular hydrogen bonds with glymes (monoglyme, diglyme or triglyme) and 0–3 water molecules by pulsed high-pressure mass spectrometry; they found that the bonding of H 3 O + typically involve two or three hydrogen bonds, and complexes of H + and H 3 O + can be stabilized by interactions with bond dipoles of free ether groups of glymes and crown ethers whilst such a stabilization is enhanced by the decreasing constraints on the geometries of polar groups. Anomalous conformational behaviors of short glymes [CH 3 (OCH 2 CH 2 ) m OCH 3 with m = 2–6] in water were studied by FT-IR 30 and Raman spectroscopy; 31 both methods indicate that poly(ethylene oxide) chain progressively prefers the gauche ( g ) conformation for the OCH 2 –CH 2 O segment at the first stage, but this direction of the conformational preference is reversed for concentrations lower than a particular solution composition. Such an anomaly can be attributed to specific interactions and/or structures relevant to the glyme-water system.…”
Section: Physicochemical and Metal Complexing Properties Of Glymesmentioning
confidence: 99%
“…Meot-Ner et al 29 examined the complexing of H + from the formation of intramolecular or intermolecular hydrogen bonds with glymes (monoglyme, diglyme or triglyme) and 0–3 water molecules by pulsed high-pressure mass spectrometry; they found that the bonding of H 3 O + typically involve two or three hydrogen bonds, and complexes of H + and H 3 O + can be stabilized by interactions with bond dipoles of free ether groups of glymes and crown ethers whilst such a stabilization is enhanced by the decreasing constraints on the geometries of polar groups. Anomalous conformational behaviors of short glymes [CH 3 (OCH 2 CH 2 ) m OCH 3 with m = 2–6] in water were studied by FT-IR 30 and Raman spectroscopy; 31 both methods indicate that poly(ethylene oxide) chain progressively prefers the gauche ( g ) conformation for the OCH 2 –CH 2 O segment at the first stage, but this direction of the conformational preference is reversed for concentrations lower than a particular solution composition. Such an anomaly can be attributed to specific interactions and/or structures relevant to the glyme-water system.…”
Section: Physicochemical and Metal Complexing Properties Of Glymesmentioning
confidence: 99%
“…A series of the Raman and infrared spectroscopy experiments for the DME/water and low molecular weight PEO/water systems have been made by Matsuura and co-workers. These investigations reveal that the tgt conformer of DME becomes the most favorable in water solution. The reported intensity ratios of gauche and trans orientations around the C−C bond will be discussed below in our analysis of DME conformations.…”
Section: Theory Experiment and Previous Simulationsmentioning
confidence: 99%
“…Effective permeation of the resin matrix occurs under the influence of a swelling solvent leading to good exposure of reactive group for peptide bond formation or enzymatic cleavage. There is strong evidence from Raman [48] infrared spectroscopy and from molecular dynamics simulation [47] that POE forms a helix in aqueous solution. There are three possible helical conformations of PEG having the low-energy gauche conformation of vicinal oxygen -carbon bond.…”
Section: Swelling Studies Of Various Pega Supportsmentioning
confidence: 99%